Efficacy and safety of sacubitril/valsartan vs. valsartan in patients with acute myocardial infarction: A meta-analysis - Yang, Pei; Han, Yang; Lian, Cheng; Wu, Xinlei (Frontiers in Cardiovascular Medicine, 2022)
Background The angiotensin-receptor neprilysin inhibitor (ARNI) sacubitril/valsartan was shown to be superior to the angiotensin receptor blocker (ARB) valsartan in terms of reversing heart failure classification (NYHA classification), reducing N-terminal pro-brain natriuretic peptide (NT-proBNP) level and cardiovascular mortality in many studies. Yet, the efficacy of ARNI did not come from patients with acute myocardial infarction (AMI). Methods We searched databases for research published from inception to July 29, 2022, that reported cardiac reverse remodeling (CRR) or security indices. Two reviewers independently screened literature, extracted data, and assessed the risk of bias. Nine studies enrolling 1,369 patients were included to perform a meta-analysis. There were 716 patients in the ARNI group and 653 in the ARB group. Results ARNI outperformed ARBs in terms of CRR indices, with striking changes in left ventricular ejection fraction (EF) (MD: 4.12%, 95%CI: 2.36, 5.88, P < 0.0001), diameter (MD: –3.40 mm, 95%CI: –4.30, –2.94, P < 0.00001, I2 = 0%) and left atrial diameter (MD: –2.41 mm, 95%CI: –3.85, –0.97, P = 0.001, I2 = 0%), other indices there showed no significant improvements. The incidences of major adverse cardiac events (RR: 0.47, 95%CI: 0.34–0.65, P < 0.00001, I2 = 0%), the heart failure (RR: 0.37, 95%CI: 0.23–0.61, P < 0.0001, I2 = 0%), readmission (RR: 0.54, 95%CI: 0.36–0.80, P = 0.003, I2 = 29%) in the sacubitril/valsartan group were lower than the ARB group, while the incidences of cardiac death (RR: 0.56, 95%CI: 0.28, 1.09, P = 0.09), the myocardial infarction (RR: 0.83, 95% CI: 0.39, 1.77, P = 0.63), adverse side effects (RR: 1.67, 95% CI: 0.89, 3.13, P = 0.11) showed no difference. Conclusion This research indicated that early initiation of sacubitril/valsartan in patients after AMI was superior to ARBs in reducing the risks of major adverse cardiac events, heart failure, readmission, and enhancing left ventricular EF, decreasing diameter, left atrial diameter. As for the other outcomes (the incidences of cardiac death, myocardial infarction, and adverse side effects), sacubitril/valsartan demonstrated no obvious advantage over ARBs. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier [CRD42022307237].